DAMPAK SENAM AEROBIK LOW IMPACT TERHADAP TINGKAT KEBUGARAN DAN GEJALA PREMENOPAUSE - M. Kus Fitriani Fruitasari (Proceeding Seminar Nasional Keperawatan, 2017)
Premenopausal period is a stage where woman’s body starts the transitioning to menopausal period. The changes that occurred in this phase are the decline of reproductive function and also hormonal, physical and psychic changes. Some premenopausal symptoms are hot flushes, night sweat, fatigue, insomnia, anxiety, forgetfulness, easily annoyed, depression, and fitness decline.One way to improve fitness level and reduce the premenopausal symptoms is low impact aerobic exercise. Aim of this study is to identify the effect of low impact aerobic exercise on fitness level and premenopausal symptoms of premenopausal women. The type of this study was pre-experimental quantitative with Static Group Comparison/Posttest Only Control design. The total respondent was 96 premenopausal women in Kelurahan Sukajaya Palembang. Data collection was conducted using questionnaire of premenopausal symptoms and the assessment of fitness level used Kasch Step Test method. Data analysis of the distinction fitness level of respondents in intervention and control groups used Chi-square test, while the analysis of premenopausal symptoms used independent t test. Fitness level intervention group higher than fitness level of control group and premonopausal symptoms lighter than premenopausal symptoms of control group. Fitness level and premenopausal symptoms of respondents in control group and intervention group showed significant difference with ρ=0.00 (ρ